RUANG INTERAKTIF-KREATIF DI KEMANG - Sudarmaya Fauzi; Doddy Yuono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Over time, the growth of the city increasingly triggers a diversity of activities that take place. One tendency of urban community activities is the need to exchange experiences and obtain a comfortable place to socialize and exchange experiences. These activities are no longer carried out at home or in the office, but in a place called Third place. Kemang is an area that was once a settlement now a commercial center called the "modern village". Over time kemang became a commercial area dominated by creative industries. The many types of creative activities lead to the behavior of people who tend to be in groups. This is very regrettable for the community because this creative activity is very important for people who want to learn or know it by exchanging experiences between art practitioners and the public. But in Kemang there is no place or place for the community to exchange experiences. The presence of Interactive-Creative Spaces in Kemang to meet the needs of community of Kemang related to art activities. With the hypothesis testing method and carried out by conducting surveys in the field, conducting interviews with relevant parties then making observations, collecting data, comparing field results with existing standards and determining the results. This program presents a program space that connected each other making it easier for visitors to access and also helps with the purpose of displaying and inviting visiting visitors to provide forums and facilities for people who want to develop their creativity. ThisInteractive-Creative Space is expected to provide a Third Place for people who want to exchange experiences with a comfortable and facilitated one. Keywords: Art container; Creative Industries; Public Space; Third Place AbstrakBerjalannya waktu, pertumbuhan kota semakin memicu keragaman kegiatan.. Salah satu kecenderungan kegiatan masyarakat kota adalah kebutuhan untuk bertukar pengalaman dan memperoleh tempat yang nyaman untuk saling bersosialisasi dan bertukar pengalaman. Kegiatan‐kegiatan tersebut bukan lagi dilakukan di rumah ataupun di kantor, melainkan pada suatu tempat yang disebut ruang ketiga (Third place). Kemang merupakan Kawasan yang dahulunya pemukiman kini menjadi pusat komersil yang disebut “kampung modern”. Seiring berjalannya waktu kemang menjadi daerah komersil yang di di dominasi dengan industri kreatif. Banyaknya macam aktifitas kreatif ini menimbulkan prilaku masyarakat yang cenderung berkelompok. Hal ini sangat di sayangkan bagi masyarakat karna aktifitas kreatif ini sangat berperan bagi masyarakat yang ingin belajar dengan bertukar pengalaman antar pelaku seni dan masyarakat. Hadirnya Ruang Interaktif-Kreatif di Kemang bertujuan untuk memenuhi kebutuhan atau tuntutan masyarakat Kemang terkait aktivitas berkesenian. Metode Pengujian terhadap hipotesis‐hipotesis dan dilakukan dengan melakukan survei ke lapangan, melakukan wawancara baik kepada pihak terkait kemudian melakukan observasi, mengumpulkan data, membandingkan antara hasil lapangan dengan standar yang ada dan menentukan hasil. proyek ini menyajikan program ruang yang berkaitan satu sama lain sehingga memudahkan pengunjung untuk mengakses dan juga berinteraksi dengan objek yang di pamerkan dan mengajak pengunjung yang berkunjung memberikan wadah dan fasilitas bagi masyarakat yang ingin mengembangkan kreatifitasnya. Ruang Interaktif-Kreatif ini diharapkan dapat memberi wadah atau tempat ketiga bagi seluruh kalangan masyarakat yang ingin bertukar pengalaman dengan suasana yang nyaman dan terfasilitasi.